Self-Compassion in the Adaptation Skills of Migrant Students in Yogyakarta - Aktafian, Algifari (LifeSciFi, 2025)
Many students face challenges when adapting to a new environment, managing academic pressure, and navigating social changes. This study aims to understand the meaning and experience of self-compassion among migrant students. Using a qualitative approach with a case study design, this study explores how students interpret self-compassion when facing adaptation challenges, academic pressure, and changes in the social environment. Data were collected through observation, structured interviews, and documentation, then analyzed using the interactive model of Miles and Huberman. The results show that self-compassion plays a significant role in helping students overcome difficult times, improve their adjustment skills, and build emotional well-being. This study also identifies internal and external factors that influence self-compassion and describes key aspects such as self-kindness, common humanity, and mindfulness. Despite the growing interest in self-compassion, few studies have focused specifically on the experiences of migrant students facing adaptation and academic challenges. These findings are expected to contribute to the development of theoretical and practical understanding of the importance of self-compassion for migrant students, providing insights for educators and counselors to support students’ emotional well-being and adjustment.